Jerusalem, Jerusalem : how the ancient city ignited our modern world - Carroll, James, 1943- (Boston : Houghton Mifflin Harcourt, 2011)
Traces the evolution of the belief that Jerusalem is the center of the Christian, Jewish, and Muslim religious worlds and argues that this fixation is a main cause of the modern-day Israeli-Palestinian conflict.
Includes bibliographical references (p. 382-393) and index.
Includes bibliographical references and index.
Keywords: Jerusalem -- History; Jerusalem -- Description and travel; Jerusalem -- Religion; Jerusalem -- Ethnic relations